Tense Errors in Albanian Speakers Learning English (L2) - Këpuska, Arta; Toçi, Arta (Advances in Social Sciences Research Journal, 2024)
Albanian students learning English as a Second Language (ESL) face considerable challenges with the English tense system due to significant grammatical differences between the two languages. This study examines the specific difficulties that Albanian ESL learners in Kosovo experience with tense usage, drawing on responses from both questionnaires and written compositions. The results reveal a high frequency of errors, particularly in the Past Simple, Present Simple, Present Perfect, Past Perfect, and Future Simple tenses. The most common errors were related to incorrect tense construction. The frequent mistakes in the Past and Present Simple tenses suggest that native language interference and the overgeneralization of English rules contribute significantly to the learners' struggles. The study calls for further research, especially longitudinal and oral-based studies, to better understand these issues and to develop more effective teaching strategies to help Albanian learners improve their command of English tenses.